Modelo de dados para SPED baseado em XBRL GL - LUCIANO, José Geraldo (2015)
The project SPED (Public Digital Bookkeeping System) has been leading to significant changes in the financial processes and relationships between companies, software developers, accounting firms and regulatory government agencies. It is a new fiscal paradigm which has brought significant changes in business routines. Currently, the SPED project consists of twelve projects: NF-e (Electronic Invoice), CT-e (Electronic Freight), NFS-e (Electronic Invoice Services), EFD-Fiscal Sped, EFD-Contributions, ECF-Fiscal Accounting Bookkeeping, FCONT-Bookkeeping Balance Sheet and Profit, ECD-Bookkeeping Digital, NFC-e (Electronic Invoice Consumer), MDF-e (Electronic Manifest Fiscal Documents), e-Social and e-Financial. Seven of these projects generate their transactional files in XML format. Others of them generate their transactional files in ASCII standard text format. Besides the absence of a pattern in the data representation it was found duplicate concepts over conceptual structures of each project. The lack of standardization affects the IT area affecting the interoperability between systems. In this context, it causes an increase in the cost of development and maintenance of systems, as well the development of various interfaces to solve the problem of interoperability and the low quality of data. Consequently, this affects business area since the information is inaccurate and it’s not always available. This scenario has become an obstacle for the implementation of audit procedures. This paper presents, as a effort to standardization, the development of a data model for SPED based on XBRL GL, which is called XBRL SPED taxonomy. To create this taxonomy is presented a process model for its development. It is expected that the proposed model allows organizations can have: (i) easier generating and transparency of information; (ii) increasing flexibility and exchange of information between the entities covered by the project, i.e. government and society, (iii) so do interoperability between SPED projects as well; (iv) facility over validation and consolidation of data according to the rules imposed on each project; (v) support continuous auditing processes and monitoring of the database and documents produced. This possibilities may be important contributions to software application developers. To evaluate the proposed data model an example of this taxonomy is presented , in which a simulation is done over files produced by SPED projects. The used example allowed infer that the proposal objectives have been achieved.